2020
DOI: 10.1021/acsaelm.0c00604
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Mechanical Durability of Stretchable Charge-Trap Memory Transistors with Engineered Wavy-Dimensional Structures

Abstract: Charge-trap memory thin-film transistors (CTM-TFTs) were fabricated with wavy-dimensional structures, and their device performances were demonstrated under mechanically stretching conditions. The fabricated CTM-TFTs obtained a wide memory window of 23.8 V, a steep subthreshold swing of 0.31 V/dec, and a large memory margin (106) with program pulses as short as 1 μs. Furthermore, the total variations in device parameters could be suppressed within a range of <12% even under stretching conditions with a prestrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Based on the observed result, it is indicated that the organic passivation film enables the reduction of the mechanical stress applied to the inorganic material layer under both bending and stretching conditions. Kim et al fabricated a charge trapping memory thin-film transistor (CTM TFT) with a wavy-dimensional structure using IGZO and zinc oxide (ZnO) (Figure 3h-j) [64]. IGZO was used as the channel layer, and ZnO was used as the channel trap layer.…”
Section: Stretchable Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the observed result, it is indicated that the organic passivation film enables the reduction of the mechanical stress applied to the inorganic material layer under both bending and stretching conditions. Kim et al fabricated a charge trapping memory thin-film transistor (CTM TFT) with a wavy-dimensional structure using IGZO and zinc oxide (ZnO) (Figure 3h-j) [64]. IGZO was used as the channel layer, and ZnO was used as the channel trap layer.…”
Section: Stretchable Devicementioning
confidence: 99%
“…Figure 3. (a) Photograph of the IGZO TFT device at strain condition; (b) The evolution of wrinkles at different stretching values is shown (0%); (c) The evolution of the wrinkles at different stretching values is shown (5.1%); (d) Transfer curve during the PBS tests with a lapse of stress time in prestrain of 50% (adapted from[60] with permission from American Chemical Society); (e) Crack formation near its channel region in strain values above 5% (scale bar: 50 µm) (adapted from[62] with permission from American Chemical Society); (f) Stretching simulation without and with an organic passivation layer; (g) Horizontal equivalent (Von Mises) stress distributions in the stretched state (adapted from[63] with permission from American Chemical Society); (h) Photograph of device surface under a mechanically stretching situation; (i) Transfer characteristics of the stretchable TFTs when pre-strain values were varied up to 60%; (j) Variations in MW and SS as a function of pre-strain value (adapted from[64] with permission from American Chemical Society).…”
mentioning
confidence: 99%
“…From a structural point of view, prestrain stretchable TFTs were reported to produce a wavy structure. , These TFTs are fabricated by transferring polyimide (PI) with TFTs after prior stretching of the elastic substrate. However, it is difficult to form a uniform wavy structure, and nonuniformly strained TFTs can operate differently depending on the location.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a way to realize stretchable electronics by studying new substrate structures. Representative structural approaches include using a wavy dimensional substrate and partially forming flexible plastic islands on a stretchable substrate with elastic interconnects. Some studies have used both wavy elastomeric substrates and partially formed rigid island region to improve elongation. …”
Section: Introductionmentioning
confidence: 99%
“…To form a wavy structure on substrate, the flexible/stretchable device is generally fabricated on a prestrained stretchable substrate. ,, The prestrained substrate naturally has a wavy shape after removing the external elongation force following upper circuit fabrication when the transfer process is completed. The circuit is usually fabricated on the PI film and transferred together with PI.…”
Section: Introductionmentioning
confidence: 99%